Does monetary policy stabilize the exchange rate following a currency crisis? - Goldfajn, Ilan (2003)
Provides evidence on the relationship between monetary policy and the exchange rate in the aftermath of currency crises. Analyzes a large dataset of currency crises in 80 countries for the period 1980-98.